Hyperthermia for Maligant Brain Tumors: A New Heating Technique - Satoh, Toru; Nishimoto, Akira; Moriyama, Eiji; Matsumi, Nobuhiko; Furuta, Tomohisa; Tamiya, Takashi; Matsumoto, Kengo; Shiraishi, Tetsuya (Nihon Haipāsāmia Gakkai shi, 1987)
Hyperthermia has emerged as a promising alternative or adjunct to other forms of brain tumor therapy. Interstitial microwave irradiation is an effective method of inducing localized brain hyperthermia. However, one of the problems of this technique is the overheating of the tissue adjacent to the antenna. In this study, a cooling system for interstitial microwave antenna was developed for the purpose of making more uniform and accurate heating by elimianting this overheating. The ability to generate more uniform hyperthermic field was evaluated in normal monkey brain. Ten brain hyperthermia trials have been performed in 5 Japanese monkeys. Under general anesthesia and controlled respiration, a perieto-occipital craniectomy of 4 × 4 cm in size was performed. The antenna cooling system was made of silicon tube of 5 mm in outer diameter. The microwave antenna of 1.5 mm in diameter was inserted into the brain with the system at the depth of 2 cm. The antenna was cooled by cold water perfusing in the cooling system. The brain tissue was heated by 2450 MHz microwave irradiation with net forward power of 10 W. Temperature distribution was mapped using nonperturbing thermocouples. This distribution with the cooling system was compared with that of without the cooling system. Using the same net forward power, the maximum cross-sectional diameter of brain heated to 42°C or above was roughly equal (about 2.6 cm in diameter) regardless the existence of the cooling system. However, this cooling system prevented the rapid radial fall off in temperature by changing the water flow volume in the system. This study shows that this cooling system enables more uniform and accurate heating with the interstitial microwave antenna and may be applied for clinical use.